Effects of montelukast sodium on tendon healing: An experimental study - AKAKIN, DİLEK (SPRINGER HEIDELBERG, 2013)
Introduction: Montelukast sodium (MS) a selective leukotriene antagonist of the cysteinyl leukotriene receptor, has been used in the treatment of asthma and allergic rhinitis. In this study, we evaluated the effect of MS on the early inflammatory phase (histological) of nonsynovial tendon healing. Materials and Methods: Rats were divided randomly into two groups (n = 6 each). MS (Singulair) was administered to one group at 10 mg/kg/day [250 g/day intraperitoneally (i.p.)]. The control group was administered 250 g/day of 0.9% saline i.p. This nonsynovial tendon was longitudinally divided at the midportion, cut transversely and then sutured. In both groups, the rats were sacrificed by decapitation 10 days later. Results: Decreased inflammatory cell infiltration and more properly oriented collagen fibres were observed in the MS group's histopathological specimens as compared to the control group's (P < 0.05). Additionally, vascularity was decreased in the MS group. Conclusion: MS decreased tendon healing, apparently by inhibiting the early inflammatory phase of nonsynovial tendon healing.
Keywords: Achilles tendon; montelukast; rats; tendon; RECEPTOR ANTAGONIST